If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (25b + -6) + -8(3b + 3) = -7 Reorder the terms: (-6 + 25b) + -8(3b + 3) = -7 Remove parenthesis around (-6 + 25b) -6 + 25b + -8(3b + 3) = -7 Reorder the terms: -6 + 25b + -8(3 + 3b) = -7 -6 + 25b + (3 * -8 + 3b * -8) = -7 -6 + 25b + (-24 + -24b) = -7 Reorder the terms: -6 + -24 + 25b + -24b = -7 Combine like terms: -6 + -24 = -30 -30 + 25b + -24b = -7 Combine like terms: 25b + -24b = 1b -30 + 1b = -7 Solving -30 + 1b = -7 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '30' to each side of the equation. -30 + 30 + 1b = -7 + 30 Combine like terms: -30 + 30 = 0 0 + 1b = -7 + 30 1b = -7 + 30 Combine like terms: -7 + 30 = 23 1b = 23 Divide each side by '1'. b = 23 Simplifying b = 23
| 8+3(-2n-7)=-(-5-3n) | | (x+4)(3x-24)=0 | | 7(b-5)=72 | | 18+-6g=-12g | | 3px(-3)=36 | | -2(-6x-4)=8x+2(x-2) | | 3(14+-5y)-5y=10 | | Y-15x=16 | | 2(1-x)+5=3(1+x)-8 | | -6(r+8)=-96 | | 5+3(-2g-7)=-40 | | -5-4p=27 | | y(2y+4)=77 | | x+15=65 | | -10-4p=22 | | 3x+5=6x-28 | | a-8=17 | | 45p+10q= | | 5(1+2p)=7p-1 | | -15-3p=6 | | 7+4b=4(1+b)+3 | | r+16=44 | | -5g+(8-g)=12 | | -47-7m=2 | | 3x^2-7x+12.25=13.25 | | m+1+5=0 | | -5x^2+7x+2=0 | | -42-6m=-12 | | 21g-12=98 | | 28x+4= | | 8n+2n=10+5n+7n | | 6(1-5n)=-8n-38 |